La posición monetaria neta - Olivera, Julio H. G. (1968)
The present work examines the influence of the net monetary position, defined as the money supply minus the net indebtedness of the private sector. It is shown that the measures of monetary policy, by contrast with those of fiscal policy, do not alter the net monetary position. It is demonstrated also that an increase in the net monetary position, given the money supply, acts upon the price level in the same direction, whilst affecting the interest rate in the opposite direction, as compared with an increase in the money supply, given the net monetary position. In neither case the Quantity Theory holds true. Finally, the case of passive money is analysed.